Regulating Topographical Deformation Response of Liquid Crystal Coatings by Electrical Quenching of Liquid Crystal Order Fluctuation - Wei Feng (Small Structures)
Alignment of liquid crystals (LCs) is critical for actuation of LC polymer‐based devices. A common strategy to induce surface deformation in LC polymer coatings involves engineering the polymers into multidomain configurations. The application of an electric field serves as an efficient means to achieve this goal. While LCs are partially ordered fluids characterized by intrinsic dynamic disorder and order fluctuations, these fluctuations can be suppressed by electric fields, a phenomenon known as electrical quenching. However, the impact of quenching LC order fluctuations on the molecular actuation behavior of LC polymers remains insufficiently understood. Herein, the translation of the electric quenching effect on LC order from the molecular scale to the macroscopic level, with a focus on regulating the topographical deformation of polymerized LC polymer coatings, is demonstrated. The findings reveal that the suppression of monomeric LC order fluctuations through electric quenching significantly reduces the topographical deformation of the polymerized network. This advancement offers new opportunities for fabricating tunable surfaces with complex patterns, broadening the potential applications of LC‐based dynamic surfaces.